2010
DOI: 10.1097/wnr.0b013e32833ce5d7
|View full text |Cite
|
Sign up to set email alerts
|

Ocular dominance affects magnitude of dipole moment: an MEG study

Abstract: O c u l a r d o m i n a n c e a f f e c t s m a g n i t u d e o f d i p o l e m o m e n t : a n M E G s t u d y H i r o s h i S h i m a 1 , 2 , M i t s u h i r o H a s e g a w a 1 , 4 O s a m u Ta c h i b a n a 1 , 5 , M o t o h i r o N o m u r a 1 , 2 , J u n k o h Ya m a s h i t a 1 , 6 Yu z o O z a k i 3 , J u n K a w a i 3 , M a s a n o r i H i g u c h i 3 , H i s a s h i K a d o 3 D e p a r t m e n t o f N e u r o s u r g e r y, G r a d u a t e S c h o o l o f M e d i c a l S c i e n c e , K a n a z… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 17 publications
1
23
0
Order By: Relevance
“…A functional magnetic resonance imaging study showed that the DE activates more of the primary visual cortex (V1) than does the non-DE for visual stimuli ( Rombouts et al , 1996 ). Indeed, a crucial relationship between the DE and the V1 ipsilateral to the DE has been reported for visual stimuli, with the V1 ipsilateral to the DE being larger and more strongly activated than the V1 contralateral to the DE ( Erdogan et al , 2002 ; Shima et al , 2010 ).…”
Section: Introductionmentioning
confidence: 95%
“…A functional magnetic resonance imaging study showed that the DE activates more of the primary visual cortex (V1) than does the non-DE for visual stimuli ( Rombouts et al , 1996 ). Indeed, a crucial relationship between the DE and the V1 ipsilateral to the DE has been reported for visual stimuli, with the V1 ipsilateral to the DE being larger and more strongly activated than the V1 contralateral to the DE ( Erdogan et al , 2002 ; Shima et al , 2010 ).…”
Section: Introductionmentioning
confidence: 95%
“…2 The dominant eye also has been studied with neuroimaging data, showing that it activates a greater part of the primary visual cortex (V1) than the nondominant eye. 4 Other evidence 5,6 suggests that the V1 ipsilateral to DE is larger 5 and more activated 6 than the V1 contralateral to DE, suggesting a privileged relationship between DE and ipsilateral V1. Due to the crossing of the optical pathways, the V1 ipsilateral to DE initially processes information presented to the hemifield contralateral to the DE.…”
mentioning
confidence: 99%
“…It is well‐known that similar factors can influence eye dominance and the ocular dominance columns in the visual cortex, such as lack of visual input as shown in deprivation studies (LeVay, Wiesel, & Hubel, ; Shatz & Stryker, ). Neuroimaging studies have shown that V1 ipsilateral to the dominant eye is larger (Erdogan, Özdikici, Aydin, Aktas, & Dane, ) and more highly activated when the dominant eye was stimulated than when the nondominant eye was stimulated (Shima et al., ). This suggests that there is a particular relationship between the dominant eye and ipsilateral V1.…”
Section: Individual Variability In Ntasmentioning
confidence: 99%
“…Interestingly, using magnetoencephalography, Shima et al. () found that V1 showed higher activation when the dominant eye was stimulated (by presenting a reversing checkerboard stimulus) than when the nondominant eye was stimulated; but only when the stimulus was presented in the nasal hemifield. This suggests that the relationship between the dominant eye and ipsilateral V1 is strongly related to input from the temporal hemiretina.…”
Section: Individual Variability In Ntasmentioning
confidence: 99%
See 1 more Smart Citation